Investigation of Graphene Dispersion From Kelly Sideband in Stable Mode-Locked Erbium-Doped Fiber Laser by Few-Layer Graphene Saturable Absorbers - Chen, Hou-Ren; Tsai, Chih-Ya; Chang, Ching-Yang; Lin, Kuei-Huei; Chang, Chen-Shiung; Hsieh, Wen-Feng (My University, 2015)
In this paper, stable passively mode-locked fiber lasers (MLFLs) constructed using graphene saturable absorbers (SAs) with different layer numbers of similar to 1 to similar to 15 have been reported. The flat linear transmission spectrum in the range from 1540 to 1580 nm without any distinct absorption peak implies that the graphene SAs exhibit low dispersion in this region. Therefore, stable soliton-like pulses are generated because of negative dispersion provided by the fiber laser cavity, which requires no additional single-mode fiber (SMF) for dispersion compensation. Power-dependent transmission measurements show that the saturation intensity ranges from 1.2 to 3.2 MW/cm(2) and that the modulation depth (MD) of the graphene SAs increases with the number of graphene layers. All the samples were observed to easily mode-lock the laser with a stable mode-locking state persistently operated over hours. By analyzing the soliton Kelly sidebands, we deduced the group delay dispersion (GDD) for different layers of the graphene. The calculated results show that the variation of sample GDD is within the calculation error, indicating that the GDD of graphene is small to be negligible. This result is consistent with the experimental results reported by Chang et al. [Appl. Phys. Lett. 97, 211102 (2010)] using the phase-shift method. This study demonstrates that different layers graphene SAs have different MD contributions to the generation of laser pulses with different pulse widths.
Keywords: Fiber lasers; laser mode-locking; nanomaterials; ultrafast optics